Value of Oxygenation Index in Selecting Neonates for Thoracoscopic Repair of Congenital Diaphragmatic Hernia - Mostafa Kotb; Sherif Shehata; Sameh Shehata; Ahmed Khairi; Aliaa Rabie; Tamer Ghonaim (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2020)
Introduction: The major obstacles for routine application of thoracoscopic repair for congenital diaphragmatic hernia (CHH) in neonates include intraoperative hypercarbia, acidosis and conversion to open surgery. Therefore, strict preoperative selection criteria should be followed for successful primary thoracoscopic repair of the diaphragm and achievement of minimal conversion rate. Materials and Methods: A prospective study was conducted from April 2016 to March 2018, where all neonates confirmed to have CDH were assessed by a specialized anaesthesia team for the possibility of undergoing thoracoscopic repair. In order to assess the severity of persistent pulmonary hypertension (PPH), oxygenation index (OI) was used and babies who had OI <5 were considered to have mild pulmonary hypertension; and consequently underwent thoracoscopic repair. Results: Twenty nine CDH cases met the selection criteria; hence, they underwent thoracoscopic repair. Primary diaphragmatic repair was successfully performed thoracoscopically in all neonates without perioperative complication. Conversion to open repair occurred in 3 cases, with causes related to surgical factors. Recurrence was discovered in 1 case only. Conclusion: While choosing candidates for thoracoscopic CDH repair in neonates, OI is a reliable indicator as it clarifies neonates who have good preoperative pulmonary function